Środowisko naturalne jako przedmiot odpowiedzialności menedżera - Brzustewicz, Paweł (Annales. Etyka w Życiu Gospodarczym, 2011)
The responsibility that rests with the current generation, which has a duty of preserving the ecosystem for the next generations, has become not only the responsibility of governments of the particular states and politicians, but also managers and companies managed by them since the most serious contamination is a result of the industrial activity. Not negating a need of industrial activities’ development; still, one must consider a change of management’s style itself, which would; apart from the economic growth, take ethics and ecology under consideration. The managers as a organizational and social leaders must learn how to make decisions with the extremely higher caution than it has been done so far. The possibilities that they have, cause that the burden of changes leading to create, propagate, and realize the outlook that allows responsibility for the future is also on their shoulders. Therefore, we need the changes that consist in revaluing the previous anthropocentric stance in ethics into the ethics based on responsibility principle, in which the biosphere might be perceived not only as an object of man’s industrial activity, but first of all as a subject of his responsibility.